Fractional carbon dioxide laser improves nodular basal cell carcinoma treatment with photodynamic therapy with methyl 5-aminolevulinate - Lippert, Jan; Smucler, Roman; Vlk, Marek (Dermatologic surgery, 2013)
BACKGROUND: The major limitation of photodynamic therapy with 5-aminolevulinic acid (ALA-PDT) is proper photosensitizer penetration. The nodular form of BCC (nBCC) is perceived as a contraindication to ALA-PDT because the tumor layer is thicker than 2 mm. We have improved on the results of previous studies that used an ablative laser to limit tumor thickness. A fractional laser produces skin microtubules that can improve the penetration of ALA into tumors. OBJECTIVE: To evaluate the use of a fractional laser as pretreatment before ALA-PDT for nBCC treatment in an 18-month single-blind clinical trial. METHODS: Fifty-six verified nBCCs were ablated using a diode laser under ultrasound control. Half of the tumors were treated 3 weeks later using a fractional carbon dioxide laser, and the other half were treated using curettage (control). We then immediately treated with ALA-PDT. Fluorescence and photography were evaluated and compared each month, and a final histopathologic examination was performed. RESULTS: Fifty-two of 56 nBCCs in the fractional laser treatment group responded to ALA-PDT, compared with only 45 of 56 in the control group. Fluorescence was higher in 53 cases in the treatment group; 3 cases demonstrated the same fluorescence level in both groups. Healing took longer in the treatment group, and there were more side effects. CONCLUSION: Fractional laser pretreatment increases the fluorescence and clinical effectiveness of ALA-PDT for the treatment of nBCC.
Keywords: Female; kombinovaná terapie; mikrotubuly; bazocelulární karcinom; kyselina aminolevulová; výsledek terapie; invazivní růst nádoru; ženské pohlaví; Neoplasm Recurrence, Local; lidé; Photochemotherapy; Photosensitizing Agents; Treatment Outcome; Lasers, Gas; fotosenzibilizující látky; nádory kůže; Male; Combined Modality Therapy; Skin Neoplasms; lokální recidiva nádoru; Carcinoma, Basal Cell; Aminolevulinic Acid; lasery plynové; Microtubules; lidé středního věku; mužské pohlaví; Neoplasm Invasiveness; fotochemoterapie; Middle Aged; Humans